18F-PEG1-Vinyl Sulfone-Labeled Red Blood Cells as Positron Emission Tomography Agent to Image Intra-Abdominal Bleeding - Zhang, Xinyi; Wang, Li; Fu, Wenhui; Feng, Yue; Zeng, Chengrun; Zhou, Liu; Zhang, Tao; Xu, Tingting; Cao, Jianpeng; Li, Zibo; Chen, Yue (Frontiers in Medicine, 2021)
18F-labeled blood pool agents (BPAs) have attracted great attention for identifying bleeding site. However, many BPAs are not sufficiently evaluated partially due to the limitations of labeling methods. In our previous work, we noticed that 18F-PEG1-vinyl sulfone (18F-VS) could efficiently label red blood cells (RBCs) ex vivo and in situ. However, its application as BPA is not fully evaluated. In this study, we systematically explored the feasibility of using 18F-VS-labeled RBCs as a PET BPA for intra-abdominal bleeding diagnosis. In brief, we first optimized the labeling conditions, which lead to 80% labeling yield of RBCs after incubating with 18F-VS in PBS at 37 °C for 20 min. 18F-VS-labeled RBCs was found to be stable in vitro which could simplify its transportation/storage for in vivo applications. In normal rat PET study, the cardiovascular system could be clearly imaged up to 5 h post injection (p.i.). Intra-abdominal hemorrhage rat model demonstrated that the 18F-VS-labeled RBCs clearly showed the dynamic changes of extravascular radioactivity due to intra-abdominal hemorrhage. Validation in the model of gastrointestinal bleeding clearly demonstrated the great potential of using 18F-VS-labeled RBCs as blood pool agent, which could be further evaluated in future studies.